Relationship of PROP (6-n-propylthiouracil) taster status, bitter taste perception, food preferences and consumption of selected Filipino adults with type 2 diabetes mellitus - Regis, Kristine Jane F.
This study assessed the relationship of PROP taster status and bitter taste perception to food preferences and consumption of selected Filipino adults with type 2 diabetes mellitus. Food preference checklist and 3-day food record was administered to the respondents for the evaluation of their food preferences and dietary intake, respectively. Sensory evaluation of PROP/NaCl and caffeine solutions was also conducted for the determination of PROP taster status and bitter taste perception. A large proportion of the respondents were female, classified as pre-obese, and have ages from 40 to 60 y old. The population (n=50) was comprised of 24% nontasters, 26% medium tasters, and 50% supertasters. Only the preference for sweet+sour food group, some foods items (i.e. green apple, banana latundan, carrot, cauliflower, cheese, boiled egg, eggplant, papaya, pineapple, and tomato catsup), as well as the intake of niacin and ascorbic acid was reported to be significantly (p<0.05) correlated with PROP taster status. On the other hand, results showed that bitter taste sensitivity was not significantly (p>0.05) correlated to the preference for selected food items (i.e. coffee, soft drinks, and tea), while a negative (p<0.05) correlation to the intake of ascorbic acid intake was reported. In general, it was observed that the population have different food preferences and lower energy and nutrient intakes compared to non-diabetic Filipino adults, which may be attributed to the diet modifications and restrictions that diabetic patients may follow.